Analysis, design and development of a framework focused on augmented reality applications: Medical rounds case - Maldonado Flores, César Javier; Fernández-Martínez, Luis Felipe; Morales Rocha, Victor Manuel; Cesar Javier, Maldonado Flores (2021)
Augmented reality is a technology that opens doors to experience interactions with virtual and real-world elements. It provides an opportunity to acquire knowledge and practical skills through software. However, it is not an easy task to determine the qualities and features that an augmented reality framework must possess to lay the foundations to build a structure focused on augmented reality. Therefore, in this work, we propose a framework focused on augmented reality applications without a specific domain area. We conduct a review of different frameworks for augmented reality. In order to define the characteristics, components, and the overall structure of our framework, a review of the most relevant literature in the field was carried out. As a result, we designed a framework focused on augmented reality without a specific domain area. Finally, we conclude that the structures, components, and features for an augmented reality framework vary greatly depending on the requirements or characteristics used for each approach.